The Correlation between Environmental Sanitation and Stunting Management through Women's Interventions and Food Security in Pre-School Age Children - Rizdya Oktofani; Hartati Kartikaningsih; Nurul Badriyah (Jurnal Penelitian Pendidikan IPA, 2025)
Stunting is a chronic nutritional deficiency that impedes growth and affects the development of body and brain cells. Addressing stunting requires multisectoral collaboration to reduce and prevent stunting among children under 5 years old, the critical "Golden Age" period. Malang City's stunting rate was 18% in 2022, 16% in 2023, with a 2024 target of 14%. Achieving zero stunting involves a multidisciplinary approach, considering environmental, social, and economic factors within a sustainable development framework. This study examines the roles of the community, stakeholders, and government in stunting management. A quantitative approach using explanatory research was conducted on pre-school children in Karangbesuki Village, with a sample of 112 families at risk of stunting from a population of 584. Data was collected through offline questionnaires, and analysis was performed using SEM-PLS software. The study found that environmental sanitation had no significant direct effect on stunting management but positively influenced women's intervention and food security. Both women's intervention and food security significantly impacted stunting management. Furthermore, women's intervention and food security played a perfect mediating role in the relationship between environmental sanitation and stunting management. Future research should consider expanding the sample size and exploring additional independent variables beyond the current framework.